To what extent do teaching strategies used by the teachers in the semesters IV, VI, and VIII of the b.a in the teaching of english influence the critical thinking skills development of students from the Foreign Languages Department at the University of El Salvador? - Amaya Torres, Oscar Gilberto
This final report presents all the aspects concerning the research carried out by the team of undergraduate students of the B.A in the teaching of English. The topic that the team investigated about is “Critical Thinking Skills Development” Since this was an exploratory research, the team intended to explore how the teaching strategies used by the teachers in the semesters IV, VI and VIII of the B.A in the teaching of English influenced in the development of the students’ thinking abilities. Indeed, the main objective of this study was to determine the extent to what the teaching strategies used by the teachers in the semesters IV, VI and VIII of B.A in the teaching of Englishinfluencedin the development of students thinking abilities. There is no doubt that university students are expected not to be passive thinkers, accepting everything they are told, but rather, critical ones who analyzed, question and draw reasonable conclusions about the issues present in the society. However, in the reality, many university students are not prepared to face such issues because of the lack of instruction they have had during their learning and teaching process. The team carried out the research during the semester II-2013 in the Foreign Language Department in order to know whether the teaching strategies used by the teachers in the semesters IV, VI and VIII of the B.A in the teaching of Englishwould be useful to overcome this problematic. The sample treated was composed of 225 students who represent the 30% of the total population, who were taking from the different content subjects coursed in the semesters IV, VI and VIII of the B.A in the teaching of English, and 16 teachers who were teaching the different subjects taken at the same time. The research has three stages: the diagnostic test, which was taken by students, meaning 30% of the students per subject in the semesters IV, VI and VIII of the B.A in the teaching of Englishin order to measure their critical thinking skills development. Besides that, the team passed a face to face interview to the teachers, who were teaching the different courses during the semesters IV, VI and VIII. The interviews were recorded in order to keep a track of their opinions and determine whether the teaching strategies used by the teachers were or were not oriented to develop critical thinking skills. Finally, the team used checklist that was completed by the observers focused in the teaching strategies used by the teacher in 19groups involved in the research, this was done in order to explore how the teaching strategies used in the classroom influence in the developing students’ thinking abilities. The results were acceptable for the team since according to the data collected does exists a slight influence of the teaching strategies used by the teachers in the classroom and the students’ critical thinking skills development. But probably as teachers had not found the best link between the material and how to use Critical Thinking abilities, in order to have students not only learn or memorize the material but also to adapt it to the real world.